Role of Hand Hygiene Ambassador and Implementation of Directly Observed Hand Hygiene Among Residents in Residential Care Homes for the Elderly in Hong Kong. (27th February 2018) - Cheng, Vincent C. C.; Chen, Hong; Wong, Shuk-Ching; Chen, Jonathan H. K.; Ng, Wing-Chun; So, Simon Y. C.; Chan, Tuen-Ching; Wong, Sally C. Y.; Ho, Pak-Leung; Mody, Lona; Chan, Felix H. W.; Wong, Andrew T. Y.; et al.
Abstract : OBJECTIVE: Multidrug-resistant organisms (MDROs) are increasingly reported in residential care homes for the elderly (RCHEs). We assessed whether implementation of directly observed hand hygiene (DOHH) by hand hygiene ambassadors can reduce environmental contamination with MDROs. METHODS: From July to August 2017, a cluster-randomized controlled study was conducted at 10 RCHEs (5 intervention versus 5 nonintervention controls), where DOHH was performed at two-hourly intervals during daytime, before meals and medication rounds by a one trained nurse in each intervention RCHE. Environmental contamination by MRDOs, such as methicillin-resistant Staphylococcus aureus (MRSA), carbapenem-resistant Acinetobacter species (CRA), and extended-spectrum β-lactamse (ESBL)–producing Enterobacteriaceae, was evaluated using specimens collected from communal areas at baseline, then twice weekly. The volume of alcohol-based hand rub (ABHR) consumed per resident per week was measured. RESULTS: The overall environmental contamination of communal areas was culture-positive for MRSA in 33 of 100 specimens (33%), CRA in 26 of 100 specimens (26%), and ESBL-producing Enterobacteriaceae in 3 of 100 specimens (3%) in intervention and nonintervention RCHEs at baseline. Serial monitoring of environmental specimens revealed a significant reduction in MRSA (79 of 600 [13.2%] vs 197 of 600 [32.8%]; P <.001) and CRA (56 of 600 [9.3%] vs 94 of 600 [15.7%]; P =.001) contamination in the intervention arm compared with the nonintervention arm during the study period. The volume of ABHR consumed per resident per week was 3 times higher in the intervention arm compared with the baseline (59.3±12.9 mL vs 19.7±12.6 mL; P <.001) and was significantly higher than the nonintervention arm (59.3±12.9 mL vs 23.3±17.2 mL; P =.006). CONCLUSIONS: The direct observation of hand hygiene of residents could reduce environmental contamination by MDROs in RCHEs. Infect Control Hosp Epidemiol 2018;39:571–577